A contemplação à luz da categoria da Primeiridade na Filosofia de Peirce - Soares, Adílio Ferreira (2016)
This work aims to make some considerations about the role of Contemplation as an experience of phenomenological Firstness within the thinking of the American philosopher Charles Sanders Peirce. In order to achieve this objective a description of the Science called Phenomenology is proposed. Phenomenology or Phaneroscopy is the first and most fundamental Science that composes the Philosophy within the authors’ systematic thinking, which also includes the Normative Sciences and the Scientific Metaphysics, on which will be made very brief considerations here, but of great importance. Through the understanding of the importance and the scope of Peirce’s Phenomenology, the focus here shall be in a more detailed manner on that which is called its first category, Firstness. In doing so, the experience of Contemplation shall be dealt as a privileged form of pure experience of such category, with the description of some of its characteristic elements